(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Mastering English in this global age is essential to prepare students to compete at the international level. The preparation according to some experts should be started since the primary school stage. However, not all primary schools in Indonesia, particularly in Manado, North Sulawesi have the privilege to have the English Language taught properly in schools. The case lies with one of private primary schools in Malalayang, Manado that is at SD GMIM 07 Malalayang. The primary school has lacked English teachers for quite a while and as a result, the students have been taught by other subject teachers or many times, there were not any English lessons taught for the students. Therefore, to bridge this gap, a community service (PKM) was carried out at the school in a form of English training given to the 5th graders of the school for 10 times. The approach used for the teaching practices was an eclectic approach coupled with communicative approach and other combinations of methods necessary to teach to young learners with very low level of English proficiency. Methods such as Total Physical Response (TPR), Audio Lingual Method (ALM), Communicative Language Teaching (CLT), Task-based Learning (TBL), and Desuggestopedia were implemented in the classroom. Delivered with games, songs, and gestures, the English training was received enthusiastically and excitingly by the students. The result of the vocabulary test achievement at the end of the training was proven not disappointing, that is 73, which is quite good, considering the fact that the students’ English mastery is still very low at the beginning of the training.